China-Brazil technical cooperation: An analysis of the Incorporation Movements of the State Grid Corporation in the Brazilian Energy Sector - Alexandre Cesar Cunha Leite; Gary Rainer Chumacero Vanderlei (Revista Internacional de Cooperación y Desarrollo)
Structured on the methodology of Process Tracing, this article analyzes the China – Brazil technical cooperation in energy matters, after the first decade of the 2000s. Through a theoretical literature review and a documentary analysis, this research begins by presenting important concepts to understand the evolution and approximation of the Sino-Brazilian relationship until the middle of the new millennium, exposing some background of this partnership discussed by the stigma of the South - South cooperation. The study follows with a deepening about the history of technical cooperation in the energy sector, showing central characteristics of this interaction and possible mutual interests between China and Brazil. The article concludes with a reflection related to some challenges and cooperation opportunities observed in the sector, discussed from the analysis of the insertion of the State Grid Corporation in the Brazilian energy sector between 2010 and 2016.